Reforming of bioethanol in the system with reverse vortex air/Сo₂ flow of “Tornado” type with liquid electrode - Nedybaliuk, O.A.; Solomenko, Ol.V.; Chernyak, V.Ya.; Martysh, E.V.; Lisitchenko, T.E.; Simonchik, L.V.; Arkhipenko, V.I.; Kirillov, A.A.; Liptuga, A.I.; Belenok, N.V. (Вопросы атомной науки и техники, 2012)
In this paper we studied the reforming of bioethanol using the combined system that includes a plasma processing and handling in the pyrolysis chamber. As the plasma source was used plasma-liquid system with back-vortex flow of gas (a mixture of air and CO₂) and liquid electrode. Carbon dioxide was added in reforming the system to influence the plasma-chemical processes in the conversion of hydrocarbons. As the working fluid was used ethanol solution in distilled water (ratio C₂H₅OH/H₂O = 1/9,5). The system was investigated by emission spectroscopy, current-voltage characteristics, gas chromatography.